THE IMPLEMENTATION ANALYSIS OF ISMA’ WA TAKALLAM METHOD IN LEARNING SPEAKING SKILL FOR NON-ARABIC SPEAKERS AT MA’HAD MU’ALLIMIL QURAN, EGYPT - Tsara Aliya Salsabila; Maman Abdurrahman; Mohamad Zaka Al Farisi (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This research aimed to analyze the implementation and evaluation system of Arabic teaching using Isma 'wa Takallam method in improving Arabic speaking skill. The method used in this research was descriptive method with qualitative approach through observational research. The subjects were 2 students who participated in Sandwich program in Egypt. The study was conducted in Ma'had Mu'allimil Quran, Giza, Egypt. The instruments used were observation, interview, and documentation. The data obtained were analyzed using Miles and Huberman model. The results indicated that the process of teaching Arabic using this method through three stages, namely: (1) Nurul Bayan learning (learning the pronunciation of hijaiyyah, spelling Qur’an verses, and tajweed), (2) learning Arabic (basic rules, muhadatsah, reading Arabic texts, and Arabic poetry), and (3) practice speaking Arabic, both inside and outside the classroom. The evaluation system used was oral test conducted during the learning process and at the end of the program.Abstrak:Penelitian ini bertujuan untuk mengetahui proses pelaksanaan dan sistem evaluasi pembelajaran bahasa Arab dengan metode Isma’ wa Takallam dalam meningkatkan keterampilan berbicara bahasa Arab. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif melalui studi observasi. Subjek penelitian ini adalah 2 mahasiswa yang berpartisipasi pada program Sandwich di Mesir. Penelitian dilakukan di Ma’had Mu’allimil Quran, Giza, Egypt. Instrumen yang digunakan adalah observasi, wawancara, dan dokumentasi. Data yang didapatkan dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa proses pelaksanaan pembelajaran bahasa Arab dengan metode ini melalui tiga tahap, yaitu: (1) pembelajaran Nurul Bayan (pembelajaran pengucapan huruf-huruf hijaiyyah, mengeja Al-Qur’an, dan ilmu tajwid), (2) pembelajaran bahasa Arab (kaidah dasar, muhadatsah, membaca teks Arab, dan syair Arab), dan (3) praktik berbicara bahasa Arab, baik di dalam kelas maupun di luar kelas. Sistem evaluasi menggunakan tes lisan yang dilaksanakan pada saat proses pembelajaran berlangsung dan pada akhir pembelajaran.